0–π transition induced by the barrier strength in spin superconductor Josephson junctions*Project supported by the National Key R&D Program of China (Grant No. 2017YFA0303203) and the National Natural Science Foundation of China (Grant No. 11474149). (September 2018) - Zeng 曾, Wen 文; Shen 沈, Rui 瑞
Abstract : The Andreev-like levels and the free energy of the spin superconductor/insulator/spin superconductor junction are obtained by using the Bogoliubov–de Gennes equation. The phase dependence of the spin supercurrents exhibits a 0– π transition by changing the barrier strength. The dependences of the critical current on the barrier strength and the temperature are also presented.